Let Them Haunt Us: How Contemporary Aesthetics Challenge Trauma as the Unrepresentable - Werner, Anna-Lena (transcript, 2020)
Let Them Haunt Us analyzes contemporary aesthetics engaged in trauma and critically challenges its canonical status as »unrepresentable«. Focusing on case studies in the aesthetic practices of Janet Cardiff and George Bures Miller, Omer Fast, Forensic Architecture, and Paul McCarthy this book proposes to redefine trauma as a productive framework to exploring individual, collective, and cultural conflicts addressed in current artistic and curatorial practices. Anna-Lena Werner considers the aesthetic realm as a potential forum that provides methods of understanding the humanitarian consequences of violence and warfare, and to reveal the effects of trauma on visual culture, collective memory, and politics.